The influence of halal logo and packaging information on university students’ purchase decisions regarding ready-to-eat (RTE) products - Bin Hasri , Muhammad Syafiq Irfan; Mahmud, Maziah (Journal of Islamic, Social, Economics and Development, 2025)
This study examines the influence of the halal logo and packaging information on university students’ purchasing decisions regarding ready-to-eat (RTE) food products. Using a quantitative approach, data were collected from 130 students at Universiti Teknologi MARA (UiTM) Shah Alam through a structured questionnaire. The findings revealed that both the halal logo and packaging information significantly influence students’ purchasing behaviour, with 98.5% of respondents indicating high levels of concern for both factors. Multiple linear regression analysis confirmed that these two factors collectively explained 38.5% of the variance in purchasing decisions, with the halal logo (β = 0.472) having a stronger influence than packaging information (β = 0.350). The study provides valuable insights for food manufacturers, marketers, and policymakers regarding halal certification strategies and transparent packaging practices to effectively cater to Muslim student consumers.